BIOCOMPUTATIONAL AND PHARMACOLOGICAL ANALYSIS OF PHYTOCHEMICALS FROM ZINGIBER OFFICINALE (GINGER), ALLIUM SATIVUM (GARLIC), AND MURRAYAKOENIGII (CURRY LEAF) IN CONTRAST TO TYPE 2-DIABETES - BHOWMIK, RATUL; ROY, SHUBHAM; SENGUPTA, SOUNOK; SHARMA, SAMEER (International Journal of Applied Pharmaceutics, 2021)
Objective: This study was aimed to analyze the inhibitory effect of the flavonoid class of phytochemicals present in ginger (Zingiber Officinale), garlic (Allium sativum), and curry leaf (Murrayakoenigii) against some receptors of type-2 diabetes such as human aldose reductase receptor, mitogen synthase kinase receptor, as well as dipeptidyl peptidase receptor by implementing several in silico analysis techniques. Methods: The 3D structures of the flavonoid class of phytochemicals of all the three plants were retrieved from the PubChem database in 3D SDF format and were converted to PDB format using PyMol software. These phytochemicals were subjected to in silico tools such as SwissADME, Pre-ADMET, and iMODS web server. The PDB-IDs of the targeted receptors human aldose reductase, dipeptidyl peptidase-IV, and mitogen synthase kinase were retrieved from Protein Data Bank in PDB format. All these receptors were then prepared for docking procedure using Autodock Tools. Now, both the prepared proteins and ligands were subjected to docking analysis using Pyrex (AutodockVina). Results: Naringenin and kaempferol showed excellent docking results with the aldose reductase receptor. On the other hand, rutin showed the best docking score with dipeptidyl peptidase receptor-IV, whereas, epigallocatechin showed the best docking results with mitogen synthase kinase receptor. The ADME analysis showed that resveratrol had the best gastrointestinal absorption as well as high blood-brain barrier permeability. Conclusion: Overall, the molecular docking results when analyzed showed a good binding affinity with the targeted receptors of diabetes. The ADME analysis and molecular docking results of the phytochemicals concluded that these compounds can be used as a potential cure for treating diabetes.